Energy fluxes and vertical heat transfer in the Southern Baltic Sea - Rak, Daniel; Przyborska, Anna; Bulczak, Anna I.; Dzierzbicka-Głowacka, Lidia (Frontiers in Marine Science, 2024)
Introduction This study investigates the dynamics of energy fluxes and vertical heat transfer in the Southern Baltic Sea, emphasizing the significant role of the dicothermal layer in modulating the penetration of the thermocline and the propagation rates of thermal energy. The research aims to elucidate the complex patterns of solar energy absorption, its conversion into sea surface temperature (SST), and the transference of this energy deeper into the marine environment. Methods Data were collected through 93 monitoring cruises by the Institute of Oceanology of the Polish Academy of Sciences (IOPAN) from 1998 to 2023, using a high-resolution towed probe technique alongside Argo floats data for the Baltic Proper from 2020 to 2023. ERA5 climate reanalysis dataset and NEMOv4.0 ocean model forecasts were also utilized for a comprehensive analysis of VITE, Top Net Short-Wave Radiation, SST, and energy budget across the Southern Baltic Sea. Results and discussion The Southern Baltic Sea functions as a net energy sink, with an average energy budget of 5.48 W m-2, predominantly absorbing energy during daylight and emitting it from September to February. A 59-day lag between peak solar energy and VITE peak was observed, followed by an additional 6-day delay before peak SST. The study further reveals a 15-day delay in temperature phase shift per 10 meters depth due to the dicothermal layer's influence on thermal energy propagation, extending to 35 days in the Central and Northern Baltic. Heat transfer is significantly affected by the levels of the thermocline and halocline, with regional variations in advection-driven seasonal signals. The pronounced thermal inertia and the critical role of the dicothermal layer underscore the complexity of thermal energy distribution in the Southern Baltic Sea.